2017
DOI: 10.1155/2017/1645013
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysms of Peripancreatic Arterial Arcades Coexisting with Celiac Trunk Stenosis or Occlusion: Single Institution Experience

Abstract: Introduction. True aneurysms of peripancreatic arterial arcades (PAAAs) are rare. Most of them coexist with celiac axis stenosis/occlusion due to median arcuate ligament (MAL) compression or atherosclerosis. The aim of this study was to evaluate the cause of celiac axis lesion and characterize the anatomy of the aneurysms. These findings may have important management implications. Material and Methods. A retrospective analysis of 15 patients with true PAAAs was performed. The diagnosis was established by contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Notably, all PDAA included had various degrees of SMA or CA stenosis, which was consistent with previous findings ( 6 ). It had been reported that stenosis or occlusion of proximal intracranial arteries could lead to increase WSS at distal areas, which was associated with aneurysm formation ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, all PDAA included had various degrees of SMA or CA stenosis, which was consistent with previous findings ( 6 ). It had been reported that stenosis or occlusion of proximal intracranial arteries could lead to increase WSS at distal areas, which was associated with aneurysm formation ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…Aneurysms of the rest of visceral arteries, however, were less studied because of their rarity. An interesting phenomenon has been observed on several occasions where stenosis of the celiac axis, mostly from median arcuate ligament syndrome, could result in an increased flow through the PDA and might be associated with the development of aneurysms ( 5 , 6 ). However, the etiologies of VAA are complicated and still require investigation.…”
Section: Introductionmentioning
confidence: 99%
“…IPDA aneurysms are rare but often associated with celiac stenosis or occlusion from median arcuate ligament compression or atherosclerotic disease. [1][2][3][4] It has long been hypothesized that retrograde flow through the IPDA arcade causes enlargement of these small vessels and promotes aneurysm development. 1,2,4 However, objective proof of this hypothesis is lacking given the fact that celiac stenosis or occlusion and IPDA aneurysms are most often diagnosed concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…Other etiologies include vasculitis, fibromuscular dysplasia, and congenital collagen disorders. 5 Hemodynamically significant stenosis of celiac axis causes increased flow through the pancreaticoduodenal arterial arcade and leads to the formation of true aneurysms. Most of these patients are treated with coil embolization when symptomatic.…”
Section: Discussionmentioning
confidence: 99%